Click, Gift, Love: Mapping the Influence of Virtual Gifts on Brand Love: A PLS-SEM Analysis in the Context of Live-Streaming Platforms - Raden Muhammad Firdaus Apriharviyanto; Popy Rufaidah (Master of Management FEB ULM, 2026)
This study aims to map the influence of virtual gifts on brand love in the context of live streaming platforms. With a quantitative approach using PLS-SEM, data were collected from 200 respondents who are active users of platforms such as tiktok, youtube, and so on. The results show that the virtual gift dimensions of identification (IDE), incentive (INC), and initiative (INI) significantly influence brand love dimensions such as affection & connection (AF), commitment (COM), and consumer-brand identification (SEL). Meanwhile, direction (DIR) and constraint (LIM) dimensions had limited influence. The findings indicate that virtual gift personalization, functional incentive integration, and symbolic interaction play a critical role in building brand love. The limitation of the study lies in the dominance of the younger generation sample in West Java, so generalization requires further study. This study contributes to the digital marketing literature by mapping the multidimensional relationship between virtual gifts and brand love.